The genetic landscape of primary malignant melanoma of the cervix using integrated bioinformatics analysis and whole-exome sequencing - Zhou, Jialiu; Xu, Tian; Chen, Chujun; Ping, Yi (Frontiers in Oncology, 2025)
BackgroundPrimary malignant melanoma in the cervix (PMMC) currently has no standardized therapy. Its pathogenesis remains unclear, and the prognosis is poor. Given the high mortality of PMMC, its causes and pathogenic mechanisms need to be unraveled, and novel biomarkers must be identified.MethodsTo further understand the genomic characteristics of PMMC, whole-exome sequencing was performed on the cancerous and adjacent tissues from three patients with PMMC, and PMMC-related tumor-susceptibility genes, mutation spectrum, mutation characteristics, driver genes, and high-frequency tumor mutations were analyzed. Concurrently, SNP and copy number variation (CNV) data from melanoma patients in the COSMIC and TCGA datasets were analyzed.Key protein interactions were further validated in vitro using co-immunoprecipitation assays.ResultsThe results showed that C>T/G>A is predominant in PMMC, with mutation characteristics more closely resembling those of SBS5 and SBS40, though not completely matching those of melanoma. Comparison with the COSMIC and TCGA databases revealed overlapping genes between PMMC and melanoma, such as TP53, AHNAK2, and PMMC, as well as previously unreported mutated genes such as AKT3, SMYD4, ATAD3A, SIRPB1, XKR6, etc. In vitro experiments and co-immunoprecipitation validation revealed that P53 interacts with AKT3, SMYD4, and ATAD3A, forming a network potentially involved in the pathogenesis of PMMC. Finally, integration of significantly mutated genes and CNV analysis revealed that copy number gains may regulate the expression of SIRPB1, AHNAK2, and XKR6, thereby activating the nuclear factor kappa B (NFkB) and protein kinase (AKT) signaling pathways, which could further promote the occurrence and development of PMMC.ConclusionThis study shows that while PMMC has similarities with other melanomas, it also harbors unique mutant genes. These findings provide a basis for exploring PMMC-related molecular markers and developing personalized diagnosis and treatment plans for patients with PMMC.